Flipped classroom learning system based on guided inquiry using moodle on acid-base solutions - Vira Gita Fani; Mawardi Mawardi (Jurnal Pijar Mipa, 2022)
This study aims to develop a digital learning system that can be used during a pandemic and meet the demands of the industrial revolution 4.0 by determining its validity and practicality. The type of research in this research is Educational Design Research (EDR) using the Plomp development model. The research was conducted at a public high school (SMA Negeri 8 Padang) in the academic year 2021/2022. Data was collected using a validated questionnaire and a practicality questionnaire. The results showed that the learning system obtained average content validity of 0.87 with a valid category and average media validity of 0.88 with a valid category. The results of the practicality test for students have average practicality of 90% in a very practical category and average practicality for teachers of 92% in a very practical category. Overall, the research results show that developing a flipped classroom learning system based on guided inquiry using Moodle on acid-base solution material is valid and practical.